PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH MOTIVASI KERJA, KOMPETENSI DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI PADA KOMISI PEMILIHAN UMUM PROVINSI SULAWESI TENGGARA (The role of job satisfaction in mediating the influence of work motivation, competence and teamwork on employee performance at the General Election Commission of Southeast Sulawesi Province) - Hasriani Hasriani; Rahmat Madjid; Muhammad Masri (Pascasarjana Universitas Halu Oleo, 2021)
The purpose of this study is to examine and analyze work motivation, competence and teamwork on employee performance both directly and through mediating job satisfaction at the General Election Commission of Southeast Sulawesi Province. The research analysis unit is an employee at the General Election Commission office of Southeast Sulawesi Province. Respondents who were sampled were 132 employees. The data collection technique was carried out by distributing questionnaires. The analytical method used in testing the hypothesis is Partial Least Square (PLS). Qualitative information is used to explore additional information related to the results of hypothesis testing.The results of this study indicate that: there is a significant influence between work motivation, competence and teamwork on job satisfaction, but work motivation on performance does not have a significant effect, this is because there is a lack of communication between departments or divisions and work conflicts, so employees tend to be stressed in the face of piling up work, because the employees of the General Election Commission of Southeast Sulawesi Province have less employees, then competence on employee performance does not have a significant effect, this is because there are several concurrent jobs in completing work, causing the work to be not optimal even though the employee high competence. Meanwhile, teamwork and job satisfaction on employee performance have a significant effect. Furthermore, the mediation variable of job satisfaction can prove to be a perfect mediation variable between work motivation and competence on employee performance, while the variable teamwork on employee performance is partial mediation.